Estudo da flamabilidade e resistência à chama de compósito de poliéster insaturado e fibra da folha do abacaxizeiro (PALF) - Ribeiro, Luciene Mendes (2011)
In the present research work, composites were prepared using pine apple leaf fibres (PALF) as reinforcement with unsaturated polyester resin as matrix, incorporating with fire retardant at different compositions. The PALF was obtained from the decortication of pine apple leaves obtained from Ramada 4 from Ielmo Marinho in the State of Rio Grande do Norte. The unsaturated polyester resin and the catalyzer were bought from the local establishment. The fire retardant, aluminium tri-hydroxide - Al(OH)3 was donated by Alcoa Alumínio S.A and was used in the proportions of 20%, 40% and 60% w/w. Initially the fibres were treated with 2% NaOH for 1 hour, to remove any impurities present on the fibre surface, such as wax, fat, pectin and pectate, in order to have a better adsorption of the fibres with the matrix as well as the flame retardant. The fibre mat was prepared in a mat preparator by immersion, developed in the Textile Engineering Laboratory, at the UFRN. The composites (300x300x3 mm) were prepared by compression molding and the samples (150x25x3 mm) for analysis of the properties were cut randomly using a laser cutter. Some of the cut samples were used to measure the smoke emission and fire resistance using UL94 standard. Mechanical tension-extension and flexural properties were carried in CTGás RN and the Laboratório de Metais e Ensaios Mecânicos Engenharia de Materiais UFRN , as well as SEM studies were carried out at Núcleo de Estudos em Petróleo e Gás Natural - UFRN . From the observed results, it was noted that, there was no marked influence of the fire retardant on the mechanical properties. Also in the water absorption test, the quantity of water absorbed was less in the sample with higher concentration of fire retardant. It was also observed that the increase in the proportion of the fire retardant increased the time of burning, may be due to the compactness of the composite due to the presence of fire retardant as a filling material even though it was meant to reduce the rate of inflammability of the composite